2007
DOI: 10.1002/mnfr.200700078
|View full text |Cite
|
Sign up to set email alerts
|

Role of garlic in the prevention of ischemia‐reperfusion injury

Abstract: Garlic in different forms has antioxidant properties. These properties are shown to be due to the existence of compounds such as water soluble organosulfur compounds, S-allylcysteine and lipid soluble compounds like diallyl sulfide. The in vivo and in vitro ischemia reperfusion studies showed that prophylactic administration of aqueous garlic prior to ischemia reperfusion inhibit lipid peroxidation and prevent depletion in glutathione through its compounds that led to functional recovery. Its ability to inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 54 publications
0
53
0
Order By: Relevance
“…The current findings revealed that CRF-induced increases in renal and cardiopulmonary MDA levels, indicating lipid peroxidation and oxidative damage, 51 were ameliorated when the animals were treated with AGE. Similarly, AGE was shown to exert cytoprotective effects in different models of experimental studies 16 by preventing increases in MDA levels and preserving normal tissue morphology in rat kidney, liver, intestine, lung, and urinary bladder. 16,26,52 In the present study, AGE treatment significantly decreased MDA levels in the kidney, heart, and lung of CRF rats, probably in part, by scavenging the very reactive hydroxyl and peroxyl radicals.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The current findings revealed that CRF-induced increases in renal and cardiopulmonary MDA levels, indicating lipid peroxidation and oxidative damage, 51 were ameliorated when the animals were treated with AGE. Similarly, AGE was shown to exert cytoprotective effects in different models of experimental studies 16 by preventing increases in MDA levels and preserving normal tissue morphology in rat kidney, liver, intestine, lung, and urinary bladder. 16,26,52 In the present study, AGE treatment significantly decreased MDA levels in the kidney, heart, and lung of CRF rats, probably in part, by scavenging the very reactive hydroxyl and peroxyl radicals.…”
Section: Discussionmentioning
confidence: 97%
“…49 To our knowledge no study has studied the effect of garlic in a renal failure model so far, except for I/R studies. 16,[22][23][24]50 In the current study, the protective effect of AGE against CRF, which is associated with oxidative stress promoting the production of ROS and cytokine release, was studied. The current findings revealed that CRF-induced increases in renal and cardiopulmonary MDA levels, indicating lipid peroxidation and oxidative damage, 51 were ameliorated when the animals were treated with AGE.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of garlic in the prevention of ischemia-reperfusion injury can be demonstrated by its inhibition of angiotensin converting enzyme action thereby contributing to cardioprotective and blood pressure lowering effects [69]. A study by Ali et al [49] showed that allicin from garlic powder has both hypolipidaemic and hypotensive effects in rats fed with a high cholesterol diet.…”
Section: Bioactive Constituents With Cardiovascular and Cerebrovasculmentioning
confidence: 99%